2014
DOI: 10.1007/s00167-014-2895-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of additional acromioclavicular cerclage for horizontal stability in complete acromioclavicular separation: a biomechanical study

Abstract: The results of this study suggest that only combined AC and CC reconstruction can adequately re-establish physiological horizontal ACJ stability. Therefore, it is likely that a combined surgical procedure with double suture-button devices and AC suture tape cerclage can adequately re-establish horizontal AC joint stability in case of an acute injury (≥type Rockwood IV and may allow superior clinical outcomes for patients, especially if early functional rehabilitation is intended).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
105
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 30 publications
2
105
2
2
Order By: Relevance
“…Following the principle of internal bracing, the AC-Bridge serves as a protective stabilizer buttressing the reconstructed ACLC and limiting horizontal clavicular translation to CORACO-AND ACROMIOCLAVICULAR LIGAMENT REPAIR e159 an almost physiological extent. 7 As is known from basic biomechanical research, isolated ACLC injury already leads to significant alteration (internal and downward rotation) of scapula positioning. 12 These findings additionally support the importance of ACLC repair and stabilization in ACJ reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the principle of internal bracing, the AC-Bridge serves as a protective stabilizer buttressing the reconstructed ACLC and limiting horizontal clavicular translation to CORACO-AND ACROMIOCLAVICULAR LIGAMENT REPAIR e159 an almost physiological extent. 7 As is known from basic biomechanical research, isolated ACLC injury already leads to significant alteration (internal and downward rotation) of scapula positioning. 12 These findings additionally support the importance of ACLC repair and stabilization in ACJ reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 A recent biomechanical study showed that additional acromioclavicular cerclage limits horizontal ACJ translation to an almost physiological extent. 7 However, significant cerclage loosening occurred over time, resulting in complete consumption of its stabilizing effect. Thus the acromioclavicular cerclage may only be regarded as a temporary stabilizer, and final horizontal ACJ stability will depend on the quality of biological healing of the ACLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical technique presented in this article and in Video 1 combines the advantages of arthroscopically positioned CC stabilization with an additional suture cord cerclage of the AC joint capsule for improved horizontal stability (Table 1). 5,6 Perform glenohumeral arthroscopy to evaluate for possible associated glenohumeral lesions. Drill the horizontal tunnel for AC cerclage before the AC joint is reduced to allow better manipulation of the distal clavicle.…”
mentioning
confidence: 99%
“…10,14,20 In a recent study, Scheibel et al 21 described persistent horizontal instability in 41% cases after isolated CC double ligament stabilization. Saier et al 22 could show biomechanically that only combined AC and CC reconstruction can adequately restore physiological horizontal AC joint stability. In addition, a recently published study showed that triple-bundle reconstruction including AC graft augmentation yielded superior clinical and radiological outcome than single-bundle CC reconstruction.…”
Section: Discussionmentioning
confidence: 99%